Foreign aid and recipient countries' exports: How important are improved bilateral trade relations? - Felicitas Nowak-Lehmann D.; Inmaculada Martínez-Zarzoso; Adriana Cardozo; Stephan Klasen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper uses the gravity model of trade to investigate the link between foreign aid and exports in recipient countries and tests for the transmission channels between aid and exports/economic development in developing countries. Most of the theoretical work emphasizes the negative impact of aid on recipient countries' exports primarily due to exchange rate appreciation, disregarding the positive impact of aid linked to the income effect. The empirical findings, in contrast, indicate that the net impact of aid on recipient countries' exports is positive and that the average return for recipients' exports is about 1.50 US for every aid dollar spent. The paper also estimates the effect of different types of aid (bilateral aid [from one donor to one specific recipient, and bilateral aid from all the other donors to one specific recipient], as well as multilateral aid flowing to a specific recipient) and finds that at least two types of aid have a positive and significant effect on recipients' exports, thus ruling out a major crowding out effect. It is further found that aid is hardly export-enhancing in Africa.
Keywords: F10; F35; 330; International Tade; Foreign Aid; Recipient Exports; Real Exchange Rate